Menadione knocks out Vitreoscilla haemoglobin (VHb) - Aydin, S (Portland Press, 2003)
Genetically engineering the heterologous bacterial host with the gene (vgb) encoding Vitreoscilla haemoglobin (VHb) has been found to provide typical advantages in growth and production, and it has generally been assumed that VHb is responsible for this effect. Here, using matched strains of Escherichia coli that bear a recombinant R-amylase gene (MK57) or the R-amylase gene and vgb (MK79), we examined this assumption. Menadione, which is known to oxidize haem proteins, was tested over a range of concentrations for its effects on growth, R-amylase production, respiration and VHb function in MK57 and MK79. Active VHb accumulated, and VHb was oxidized to the inactive ferric form with the use of menadione at the concentrations of 0.5-10 mM; concentrations that had a much smaller effect on cytochrome oxidase. This decrease in active VHb in strain MK79 was correlated with a reverse in the advantage regarding R-amylase production of MK79 over MK57 seen at a menadione concentration of 0 mM, thus linking the presence of active VHb with the increase in R-amylase production. It is concluded that vgb, and not any other Vitreoscilla DNA squences on plasmid pMK79, is the source of the advantages in both the growth and product production of et-amylase in this system.
Keywords: alpha-amylase; menadione; Vitreoscillo haemoglobin (VHb)